Analysis of Information Production Systems of Animation Study Program on the School of Multi Media Website - Charles De Haan (Jurnal Imiah Teknik Studio, 2022)
Web application as a medium of communication and information is an important part of a shigher education institution. Website plays a strategic role in the existence of institutions in the world. The availability and speed of information will have an impact on decision making that is useful for the future. This study aims to analyze the quality of information production on the mmtc.ac.id website for the development of Animation Study Program website. The research was conducted using a qualitative descriptive approach with the PIECES and Fishbone analysis methods, namely diagram to analyze the information production on the website. The results of the study found that there were problems in the quality and quantity of information production about the Animation Study Program on the main website, the lack of website management personnel, and the absence of information managers specifically for the study program. Website managers need to develop a separate website as a of information medium for animation study program so that needs of communication and information for students and public can be fulfilled.Web application as a medium of communication and information is an important part of a shigher education institution. Website plays a strategic role in the existence of institutions in the world.The availability and speed of information will have an impact on decision making that is useful for the future. This study aims to analyze the quality of information production on the mmtc.ac.id website for the development of Animation Study Program website.The research was conducted using a qualitative descriptive approach with the PIECES and Fishbone analysis methods, namely diagram to analyze the information production on the website.The results of the study found that there were problems in the quality and quantity of information production about the Animation Study Program on the main website, the lack of website management personnel, and the absence of information managers specifically for the study program.Website managers need to develop a separate website as a of information medium foranimation study program so that needs of communication and information for students and public can be fulfilled.Key words: website, PIECES, Fishbone, quality, information.